Comparative evaluation of pH, bond strength and washability in four common denture adhesives in Iran - Mehran Bahrami; Maryam Memarian; Farinaz Khodadad Kashi (Tehran University of Medical Sciences, 2015)
Background and Aims: Residual ridge resorption is an unpredictable, unavoidable and time-dependent process which occurs in denture-wearing patients especially those who use mandibular dentures. This process causes more problems in mandible because of its less support, tongue forces and more resorption. Inserting implants in many of these patients requires bone grafts. Overdentures are also more expensive. Denture adhesives are the last option to improve retention and masticatory function in denture-wearers with severe resorption of alveolar ridge. Nowadays only a few denture adhesives are used in Iran and there is not much information about their standard features including, pH, bond strength and washability. The objective of this study was to examine and compare the mentioned characteristics of four denture adhesives (Professional, Corega, Fittydent and Fixodent) and to introduce the most suitable denture adhesive for clinical use. Materials and Methods: All the methodologies of ISO 10873:2010 were applied. To measure the pH value, 1±0.1g of each denture adhesive was diluted with 5g of propylene glycol and mixed with water. Using pH meter, pH of each group was measured separately for 4 times (n=4) and results were recorded. For the washability test, 4 dentures were fabricated (n=4) and each group of denture adhesives was placed on a denture according to manufacture instructions. For simulating mouth environment specimens were placed in water at 37±2 ̊C bath for 1 hour and then washed with a plastic brush. Specimens were examined for any residual adhesive and the results were recorded. For bond strength test, a sample holder was gently filled with denture adhesives and was attached to the holding arm of bond strength testing device (Santam, STM 20, Iran). Specimens were placed in 300ml water bath at 37±2 ̊C for 10 minutes, and then shaken to be dried and placed in the bond strength testing device. 10N force with 5mm/min rate was applied to the specimen. The force was maintained for 30s and then device arm was pulled back and the highest number was recorded with computer software (Santam Machine Controller v4.19, Iran). The test performed 8 times (n=8) for each adhesive and 8 results were recorded. Data were analyzed using ANOVA test for comparing the bond strength with a significant level fixed at 0.05. Results: Professional and Corega adhesives had more neutral pH than that of Fittydent and Fixodent which were more acidic. Washability test showed no remaining mass of any adhesive and there was not any statistically significant difference between groups (P>0.05). Fittydent and Corega adhesives showed higher bond strength than that of Professional and Fixodent and this difference was statistically significant (P<0.05). Conclusion: Professional and Corega adhesives had less acidity. Thus they cause less harmful effects on the oral mucosa than that of Fittydent and Fixodent and should be indicated in patients with little-tolerant oral mucousa such as diabetous, iron-deficiency anemia and hypertention. All the groups had acceptable washability. Fittydent and Corega had higher bond strength than that of Professional and Fixodent. Therefore in complete-denture-wearers who require more retention as a result of severe ridge resorption, macrotruma, and maladaptiivity, Fittydent and Corega seems to be more acceptable.